EFFECT OF ALTERNATE WETTING AND DRYING IRRIGATION REGIMES AND WEED MANAGEMENT PRACTICES ON GROWTH AND YIELD OF WET SEEDED RICE - A. MADHAVI; S. NARENDER REDDY, N. PRATHAP REDDY, G. E. CH. VIDYA SAGAR, M. YAKADRI, M. MALLA REDDY (The Journal of Research, PJTSAU, 2023)
A field experiment was carried out at College Farm, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad during rabi 2020-21 and 2021-22. The experiment was laid out in split plot design with two factors i.e., irrigation regimes (I1: Farmers practice (continuous flooding of 2-5 cm from 3-4 DAS), I2: AWDI at 5 cm depletion of ponded water, I3: AWDI at 10 cm depletion of ponded water and I4: AWDI at 15 cm depletion of ponded water) and weed management practices viz., W1: Control (Unweeded check), W2: Pyrazosulfuron ethyl (10% WP) 20 g ha-1 PE fb penoxsulam (1.02%) + cyhalofop butyl (5.1%) 120 g ha-1 PoE, W3: Pyrazosulfuron ethyl (10% WP) 20 g ha-1 PE fb penoxsulam (1.02%) + cyhalofop butyl (5.1%) 120 g ha-1 PoE + mechanical weeding at 45 DAS and W4: Weed free (mechanical weeding at 15, 35 and 55 DAS with line weeding). Among the irrigation regimes significantly higher plant height, leaf area, dry matter production, no.tillers m-2, grain and straw yields were recorded with Farmers practice (continuous flooding of 2-5 cm from 3-4 DAS) and it was on par with AWDI at 5 cm depletion of ponded water during both years of the study respectively. With respect to weed management practices Weed free (mechanical weeding at 15, 35 and 55 DAS with line weeding) resulted in significantly highest plant height, leaf area, dry matter production, no.tillers m-2, grain and straw yield and it was on par with Pyrazosulfuron ethyl (10% WP) 20 g ha -1 PE fb penoxsulam (1.02%) + cyhalofop butyl (5.1%) 120 g ha-1 PoE + mechanical weeding at 45 DAS) during 2020-21 and 2021-22.